AI techniques for reliability prediction for electronic components - Bhargava, Cherry, 1982- (Engineering Science Reference, an imprint of IGI Global, 2020)
"This book explores the theoretical and practical aspects of prediction methods using artificial intelligence and machine learning in the manufacturing field"-- Provided by publisher.
Keywords: Electronic apparatus and appliances -- Reliability.; Electronic apparatus and appliances -- Testing -- Data processing.; Electronic apparatus and appliances -- Service life.; Artificial intelligence -- Industrial applications.; elektronické knihy; electronic books